Pengelolaan Keuangan NUS: Analisis Belanja Pada Tahun Anggaran 2023-2024 - Riyanto, Nafiah Lintang; Munadi, Muhammad (PT. Cahya Edupreneur Indonesia, 2025)
This study aims to analyze the financial management of the National University of Singapore (NUS) for the 2023–2024 fiscal year using a common size analysis approach. The data were obtained from NUS’s publicly accessible financial reports. Findings indicate that the largest expenditure component is Expenditure on Manpower, accounting for 52% of the total budget. This reflects the university’s prioritization of human capital development and staff welfare. The second-largest category, Other Operating Expenditure (34–37%), includes costs related to daily campus operations. Depreciation & Amortisation Expenditure accounts for 10–11%, while Scholarships and Interest & Borrowing Costs take up smaller shares. The observed increases across several categories suggest strategic adjustments made to support institutional sustainability, operational efficiency, and educational service quality. Moreover, NUS demonstrates a strong commitment to financial transparency by consistently publishing open-access financial statements. This study contributes to the discourse on higher education financial governance and provides a reference for other institutions seeking to strengthen accountability and sustainability in their financial systems. The findings highlight the importance of transparent, well-structured budgeting in fostering trust, institutional resilience, and long-term excellence in higher education